2016
DOI: 10.1186/s12887-016-0616-8
|View full text |Cite
|
Sign up to set email alerts
|

Parents are poor at labelling wheeze in children: a cross-sectional study

Abstract: BackgroundNoisy breathing is a common presenting symptom in children. The purpose of this study is to (a) assess parental ability to label wheeze, (b) compare the ability of parents of children with and without asthma to label wheeze and (c) determine factors affecting parental ability to label wheeze correctly.MethodsThis cross-sectional study in a tertiary hospital in Kuala Lumpur, Malaysia involved parents of children with asthma. Parents of children without asthma were the control group. Eleven validated v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…It should also be noted that the reported wheezing by the caregiver may not always be accurate especially for those whose native tongue is not English. 31 Montelukast treatment decreased the wheezing score and reduced the need for inhaled β2-agonist medication in the first weeks of a recurrent wheezing illness for children 3-36 months of age. Further studies could better define the importance of wheezing episodes and burden of β2-agonist rescue events to caregivers and better define the optimal duration of montelukast therapy to achieve these benefits.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It should also be noted that the reported wheezing by the caregiver may not always be accurate especially for those whose native tongue is not English. 31 Montelukast treatment decreased the wheezing score and reduced the need for inhaled β2-agonist medication in the first weeks of a recurrent wheezing illness for children 3-36 months of age. Further studies could better define the importance of wheezing episodes and burden of β2-agonist rescue events to caregivers and better define the optimal duration of montelukast therapy to achieve these benefits.…”
Section: Discussionmentioning
confidence: 93%
“…Larger studies will be better able to control for confounding present at baseline, including the imbalance in cys_LTs levels observed in this study. It should also be noted that the reported wheezing by the caregiver may not always be accurate especially for those whose native tongue is not English …”
Section: Discussionmentioning
confidence: 99%
“…One study of Malaysian parents found that only one third correctly labeled wheeze when shown videos of isolated respiratory sounds. 4 Another study compared parental report of wheeze with physician assessment in young children at high risk of asthma, and of the cases when parents reported wheeze, only 70% were confirmed by a physician. 5 Our findings are consistent with these studies, suggesting that parents tend to overestimate the presence of wheeze in real-life scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Accuracy of caregiver report of wheeze has predominately been evaluated through the use of videos. 3,4 While such methods have allowed for standardized assessment, they are limited in indicating how well caregivers recognize wheeze in real-life scenarios. Thus, we conducted a study of over 800 children undergoing evaluation for pneumonia in order to determine the test characteristics of parental report of wheeze compared with physician assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Including children from areas free of flooding as well as a study of flood prone areas during the dry season would have provided control groups with which to better explain findings reported by this study and availed data on relative humidity of homes for the two seasons. Some studies [46][47][48] have related the presence of air pollutants such as gases, smoke, fungal spores and dust particles to development of wheezing in children. This study was, however, unable to include these kind of risk factors.…”
Section: Limitations Of the Studymentioning
confidence: 99%